Assesssment Of Heavy Metals in Sedimentary Formation of Kogi State, Nigeria - Bolade, Ayodeji Ogunkolu; Garba, A Dadan; Garba, H; E, Tokula A.; O., Idoko; F, Balogun G.; F, Enefola A.; M, Ogbole; S., Ademu; N, Ukojie L.; O, Abuh P.; Abdulateef, Ahmed (Faculty of Geography, Universitas Gadjah Mada, 2025)
Contamination of water resources by heavy metals poses significant environmental and public health challenges worldwide, especially in developing regions like Nigeria. This study investigated the concentration levels of heavy metals in sedimentary formations across selected local government areas in Kogi State, Nigeria, with the aim of assessing seasonal variations and potential health risks. Four local government areas were strategically chosen to represent major sedimentary formations in the state. Water samples were systematically collected during both dry and wet seasons, yielding a total of 60 samples per season for laboratory analysis. The samples were analyzed for 10 physico-chemical parameters, 3 biological indicators, and 10 heavy metals using standard laboratory procedures. Data were analyzed using SPSS 20.0 for descriptive statistics and further subjected to inferential statistics, including Analysis of Variance (ANOVA) and Student t-test, to assess variations across seasons and formations. Results revealed that concentrations of heavy metals such as zinc (Zn), arsenic (As), mercury (Hg), nickel (Ni), cadmium (Cd), iron (Fe), and magnesium (Mg) exceeded both WHO and Nigerian Standards for Drinking Water Quality (NSDWQ) limits, particularly during the wet season, indicating significant seasonal variability and potential ecological risks. The findings highlight the critical need for effective environmental management and pollution control measures in the study area. The study's novelty lies in its comprehensive seasonal and spatial assessment of heavy metals across sedimentary formations, providing baseline data for policymakers. In comparison with similar studies in Nigeria and globally, these results emphasize the urgent need to improve waste management practices and strengthen water quality monitoring systems. Received: 2023-07-16 Revised: 2025-01-16 Accepted: 2025-08-05 Published: 2025-08-19